STRATEGI ADAPTASI LINGKUNGAN BERDASARKAN EKOFAK CANGKANG MOLUSKA DI GUA KOTA DESA TOROBULU KECAMATA LAEYA KABUPATEN KONAWE SELATAN - Jaslim Ariandi; Abdul Alim; Arie Toursino Hadi (SANGIA: Jurnal Penelitian Arkeologi, 2024)
Gua Kota are caves that have been inhabited by humans and contain remains in the form of molluscs’ shell waste and pottery fragments. The aim of this research is to find out how Gua Kota dwellers utilize types of molluscs and to explain how environmental adaptation strategies were carried out in the past based on the types of molluscs left behind. The method used is a type of qualitative research with an ethnographic approach. The data collection methods used are divided into two, namely field data (primary) and library data collection (secondary). The analysis techniques used in this research are contextual data collection to understand the function of artifacts and ecofacts and environmental analysis and taxonomic analysis. The results of this research indicate that the Gua Kota has 18 types of molluscs that are utilized by the inhabitants of the Gua Kota as food, and one type that cannot be consumed. Among the molluscs, the most consumed by the Gua Kota residents are the Anadara Granosa, Ceminella, Teloscopium, and Circe Skripta species. These mollusc types are also the most found on the surface of the cave. In terms of environmental strategy, the Gua Kota has a strategically located area that can be used as a dwelling place. The molluscs processing techniques are divided into two categories: for food and as raw materials.